The Relationship Eating Habits and Sedentary Activities On Physical Fitness Of Students 13-15 Years - Faisol Hamid (PHEDHERAL, 2023)
This study aims to relate eating habits and sedentary activities to the physical fitness of students aged 13-15 years, the study used an observational analytic design with a cross sectional approach. Observational analytics is research that is carried out only through observation, without any intervention on the research subject. the population of this study is 288 students so that when the population is more than 100, it uses a percentage calculation with 25% so that the number of samples in the study is 72 students. The research instrument used the Adolescent Food Habit Checklist (AFHC) eating habits questionnaire, for sedentary activities using the ASAQ (Adolescent Sedentary Activity Questionnaire) questionnaire, the Indonesian Physical Fitness Test age 13 - 15 years. This study resulted in the calculation of data showing that there is a relationship between eating habits and fitness with a sig value of 0.01 ˂ 0.05, while for sedentary activities to physical fitness shows that there is a relationship based on a sig value of 0.04 ˂ 0.05. The conclusion is that there is a significant relationship between eating habits and sedentary activities on students' physical fitness.